Empowering BUMDes Guyub Rukun: Branding strategies and digital marketing for tourism village - Yuliani, Nur Laila; Afif, Naufal; Kusumaningrum, Serafica Btari Christiyani (Universitas Muhammadiyah Magelang, 2025)
The “Guyub Rukun” Village-Owned Enterprise (BUMDes) in Wringinputih Village, a buffer zone for the Borobudur National Strategic Tourism Area, possesses diverse potential business units but faces challenges due to limited promotion. This community service initiative aims to empower the BUMDes through improving human resource quality and developing branding and digital marketing for village tourism packages, including assistance for business units and MSMEs. A participatory rural appraisal method was implemented through socialization, training (waste management, branding, digital marketing), and mentoring. The results of the activities demonstrated a significant increase in waste management (including eco-enzyme production), an understanding of the importance of branding, and the adoption of digital marketing with the potential to increase income and welfare, as well as the formation of the “Borobudur Tourism Education” village tourism package, which is expected to enhance tourist attraction.